Efeitos das mudanças climáticas globais sobre a distribuição e a dispersão do lobo-marinho-subantártico Arctocephalus tropicalis (Gray, 1872) - Oliveira, Carlos de (Universidade do Vale do Rio dos Sinos, 2025)
Understanding species’ geographic distribution is essential for comprehending how environmental factors influence biodiversity patterns. By identifying the set of environmental conditions that affect this distribution, it is possible to predict changes in species abundance and spatial occupancy. However, climate change has caused abrupt shifts in distributions in both terrestrial and marine environments, representing a growing threat to biodiversity. Top predators, such as the sub-Antarctic fur seal (Arctocephalus tropicalis), are particularly vulnerable, as they rely on the abundance and location of their prey and on the stability of their breeding, foraging, and resting habitats. This study aimed to analyze, from a climate change perspective, the environmental factors that influence the distribution of A. tropicalis, with emphasis on its main breeding colonies on the Tristan da Cunha/Gough Islands (TDC/Gough) and on the species’ extra-limital occurrences along the Brazilian coast. To this end, time series (1982–2021) of oceanographic variables were evaluated in the TDC/Gough region, including sea surface temperature (SST), shifts in the Sub-Antarctic Front (SAF) and northern boundary of the Subtropical Front (STFN), and chlorophyll-a (Chl-a) concentration as a proxy for productivity. SST, SAF, and Chl-a showed significant positive annual trends, whereas STFN exhibited a negative trend, indicating a southward shift of the SAF and a northward expansion of the STFN toward the colonies. These changes may negatively impact lactating females by increasing foraging distances and reducing reproductive success. In addition, 656 records of A. tropicalis along the Brazilian coast between 1992 and 2021 were compiled and analyzed, with a predominance in the southern region (69%) and higher frequency during the austral winter months (July to September). Association models revealed that variables such as seasonality (sine and cosine), mixed layer depth (MLD), and SAF were strongly correlated with occurrence patterns. Regional variables such as Chl-a and the South Atlantic Ocean Dipole Index (SAODI) influenced records in the southern region, while the Southern Annular Mode (SAM) and the South Atlantic Subtropical Dipole Index (SASDI) affected records in the southeastern and northeastern regions. These results support the hypothesis that multiple environmental factors may differently influence the species’ dispersal routes along the Brazilian coast. Habitat suitability models indicated that the current potential distribution of A. tropicalis (suitability > 0.7) is concentrated around subantarctic and subtropical colonies but also includes areas not currently colonized, such as the Falkland/Malvinas Islands, Tierra del Fuego, southern Chile, Kerguelen Islands, southern Australia, Tasmania, and New Zealand. Projections of A. tropicalis distribution for the years 2050 and 2100, based on AR6 climate scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5), indicated a shift toward sub-Antarctic and polar regions and an increase in moderately suitable areas (0.5–0.9). However, a significant contraction in highly suitable areas (>0.9) was also projected, particularly in current breeding colonies such as TDC/Gough and Amsterdam Island. The results suggest that current breeding colonies of A. tropicalis may become less suitable as the century progresses, while new areas south of its current range may become favorable, indicating a possible geographic expansion of the species. This includes the potential overlap with other otariid species and, consequently, the occurrence of natural hybridization events, as already recorded between A. tropicalis, A. gazella, and A. forsteri on Macquarie Island. On the other hand, the colonization of South American coastal areas as new breeding sites is unlikely due to the lack of suitable ecological conditions. Factors such as the need for remote islands with rocky substrates, a prolonged lactation period, urbanized coastal zones subject to human disturbance, and the risk of pup predation by domestic dogs severely limit the species’ reproductive success in these regions. Together, the results indicate that climate change may reshape the distribution of A. tropicalis, both by altering its breeding areas and by expanding its extra-limital dispersal.
Keywords: Temperatura da superfície do mar; Frentes subantárticas e subtropicais; Clorofila-a; Ilha remota; Modelos de distribuição de espécies; Dispersão extra limite; Distribuição nas colônias reprodutoras; Ilhas Tristão da Cunha/Gough; Cenários climáticos futuros; Modelo ensemble; Adequação ambiental; Sea surface temperature; Subantarctic and Subtropical fronts; Chlorophyll-a; Remote island; Species Distribution Models; Extra-limital dispersal; Distribution in breeding colonies; Tristan da Cunha/Gough Islands; Future climate scenarios; Ensemble model; Environmental suitability; ACCNPQ::Ciências Biológicas::Biologia Geral